2006
DOI: 10.4141/s05-092
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of soil water-extractable organic C following application of dairy cattle manures

Abstract: . 2006. Dynamics of soil water-extractable organic C following application of dairy cattle manures. Can. J. Soil Sci. 86: 851-858. Water-extractable organic C (WEOC) is a determinant driver of several soil and environmental processes, and can be influenced by management practices such as organic amendment. Our objective was to study the dynamics of soil WEOC following application of liquid and solid dairy cattle manures to a loamy and a clay soil under field conditions. Manures were applied in 2 consecutive ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…Those results are in disagreement with many studies where concentrations of water‐extractable organic C were found to be greater when animal manure was applied to the soil (Gregorich et al, 1998; Chantigny et al, 2002). By contrast, Angers et al (2006) reported a low increase in soil DOC concentration after liquid dairy cattle manure was applied. They argued that rototilling for incorporation favored the adsorption of manure‐soluble C to the mineral particles.…”
Section: Resultsmentioning
confidence: 90%
“…Those results are in disagreement with many studies where concentrations of water‐extractable organic C were found to be greater when animal manure was applied to the soil (Gregorich et al, 1998; Chantigny et al, 2002). By contrast, Angers et al (2006) reported a low increase in soil DOC concentration after liquid dairy cattle manure was applied. They argued that rototilling for incorporation favored the adsorption of manure‐soluble C to the mineral particles.…”
Section: Resultsmentioning
confidence: 90%
“…It is difficult to speculate on the exact mechanisms to explain the immediacy of reduction in CWEOC, HWEOC and soil respiration after FIT. However, ploughing soils is a very specific action that involves (i) the placement of residues at depth with lower O 2 availability, which reduces the decomposition rate of organic matter and (ii), the increased contact of decomposing organic matter with newly exposed mineral surfaces, which likely favours the adsorption and retention of potentially soluble C (Angers et al, 2006;Hassink, 1997;Six et al, 2002;Stemmer et al, 1999).…”
Section: Resultsmentioning
confidence: 98%
“…This could simply be due to the decline in soil organic matter content following cultivation (Deluca and Keeney, 1993;Ghani et al, 2003). However, reductions may also be due to the improved contact of soluble C with unsaturated soil mineral surfaces following tillage (Angers et al, 2006). This contact is thought to stabilise C and to reduce its vulnerability to decomposition (Guggenberger and Kaiser, 2003;Stemmer et al, 1999).…”
Section: Introductionmentioning
confidence: 97%
“…First, we considered the number of animals (poultry, pigs and cattle) living on the catchment area and the expected amount of waste material produced by these animals (Biomasse Normandie, 2002). Secondly, a literature survey on concentrations of water extractable organic carbon (WEOC) of various animal wastes, including cattle manure (CM), pig manure (PM) and poultry litter (PL), was conducted (Bernal et al, 1998;Huang et al, 2004;Zmora-Nahum et al, 2005;Angers et al, 2006;Aira et al, 2007;Gattinger et al, 2007;Guo et al, 2009; Table 3). Some discrepancies were found between studies, however, an average WEOC concentration of 12 mg g À1 for all manure types was retained as it is in accordance with most of the reports.…”
Section: Sampling Datementioning
confidence: 99%
“…( C indicates composted manure). Note that 12 and 5 mg g À1 have been retained for WEOC values (fresh and composted manure, respectively) because they represent the means from the various cited studies (values from Angers et al (2006) and Guo et al (2009) …”
Section: Comparison Of Fluxes With Other Agricultural Watershedsmentioning
confidence: 99%